2007
DOI: 10.1002/ptr.2194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oriental herbal prescription Guan‐Xin‐Er‐Hao on coronary flow in healthy volunteers and antiapoptosis on myocardial ischemia‐reperfusion in rat models

Abstract: Ischemic heart disease (IHD) is the main cause of death and a major public health problem in the world. The traditional herbal medicinal formula Guan-Xin-Er-Hao (GXEH) has been used in China and East Asia for the treatment of coronary heart disease, however, the underlying cardioprotection mechanisms remain unclear. To make clear the antiischemic mechanism involved, GXEH was orally administered to 15 healthy volunteers. Heart rates (HR), blood pressure and coronary flow (CF) velocity before and 1 h after a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…It has been demonstrated that some TCMs have anti-inflammatory effects in CVD treatment [18,29,35]. In our previous studies, GXEH reduced infarct size by mediating lots of endogenous materials via multiple pathways to act on myocardial cells during acute myocardial infarction (AMI) in rats [12,24,36,37]. Accordingly, we speculated that GXEH might have an anti-inflammatory effect and that the anti-inflammatory effect might be one of the cardioprotective mechanisms.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…It has been demonstrated that some TCMs have anti-inflammatory effects in CVD treatment [18,29,35]. In our previous studies, GXEH reduced infarct size by mediating lots of endogenous materials via multiple pathways to act on myocardial cells during acute myocardial infarction (AMI) in rats [12,24,36,37]. Accordingly, we speculated that GXEH might have an anti-inflammatory effect and that the anti-inflammatory effect might be one of the cardioprotective mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Formula extracts were prepared as previously described [36,37]. All of the herbs were purchased from West China Hospital (Chengdu, China).…”
Section: Composition and Preparation Of Gxeh Formulamentioning
confidence: 99%
See 3 more Smart Citations